Developing a Digital Islamic Education Model: Integrating Artificial Intelligence, Islamic Pedagogy, and Digital Learning Ecosystems - Rahmat Zubandi Thahir; Hasan Baharun (DAAR EL-IDARAH: Journal of Islamic Education Management, 2026)
This study investigates the integration of Artificial Intelligence (AI) and the subsequent transformation of the digital learning ecosystem within Islamic Education (PAI) at SMA 01 Tiris. Operating within a qualitative intrinsic case study design, this research explores how modern educational technologies can be adopted without reducing the foundational spiritual and affective dimensions of traditional Islamic pedagogy. Data were comprehensively gathered using method triangulation—comprising semi-structured in-depth interviews with key institutional stakeholders, participant observations of digital classroom dynamics, and documentary analysis of digital curricula and artifacts. The collected data were analyzed interactively using the Miles, Huberman, and Saldaña framework, while scientific trustworthiness was secured via source triangulation, technical triangulation, and member checking. The empirical findings reveal that the mechanism of AI integration does not lead to institutional secularization; instead, it establishes a framework of "Guided Techno-Spiritual Symbiosis." Within this dual-layered model, AI successfully automates the profane-computational domain by providing cognitive scaffolding, while the human educator retains absolute jurisdiction over the sacred-transformational domain to nurture moral character (akhlak). Furthermore, the structural transformation of the digital learning environment introduces an "Ethical Digital Buffer" based on the prophetic principle of verification (tabayyun), which simultaneously stimulates high-order cognitive competence and digital literacy inside a controlled ethical framework. This study contributes a novel tekno-pedagogical blueprint for religious educational institutions, proving that technological modernism can be harmoniously anchored by transcendental values.